Frequency and Time Response of Power Plant Grounding System Exposed to Lightning Strike - Srete N Nikolovski; Zoran Baus; Goran Knežević (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper examines the frequency response of power plant grounding system exposed to the lightning current. Large amount of current generated by the stroke flow in the grounding system of power plant and dissipate in the soil.  The electric and magnetic field generated by such high voltages and currents may cause damage of equipment and may be dangerous for the personnel in power plant.  For the every given frequency obtained using Fast Fourier Transformation (FFT) of lightning current impulse, electromagnetic field theory approach is used to solve Maxell’s equation and compute scalar potential, electric and magnetic field. Also, the influence of the point in which lightning current is diffused in the grounding system is presented. Three dimensional plots of spatial distribution of scalar potential, electric and magnetic field are presented. The time domain response of scalar potential, electric and magnetic field on one profile is also presented.